THE ANALYSIS OF THE PREVALENCE OF PROSTATE CANCER IN THE REPUBLIC OF BASHKORTOSTAN FOR THE LONG PERIOD OF OBSERVATION - I. R. Rakhmatullina (Креативная хирургия и онкология)
The article analyzes the incidence of prostate cancer in the Republic of Bashkortostan from 1993 to 2002 and from 2003 to 2012, the levels of the primary disease, the patterns of the level, dynamics of morbidity in different years depending on age.